Les questions féministes dans les revues occitanistes des années 1968 : entre revendications et négociations - Camille Courgeon (Lengas)
This article looks at how feminist issues were addressed in the Occitan movement of the Long 1968 period. Drawing on three journals that were close to the political and cultural sides of the movement, Lutte occitane, Per noste, and Fòrabanda, the article shows how the feminist positions of each contributed to bringing Occitanism into dialogue with the other politically committed left-wing social movements of the period, such as the feminist ones. It also analyses how the editorial particularities and positions of each group on feminist questions are as dependent on the aims of the journals as they are on individual personalities who contibute to their production. Finally, this article discusses how the journals bear witness to the negotiations and debates around these issues in Occitanism during the period, as much as they contribute to disseminating feminist and occitanist demands and creating new frameworks for reflection for the movement.